Role of metallothioneins as danger signals in the pathogenesis of colitis. Issue 1 (24th February 2014) - Devisscher, Lindsey; Hindryckx, Pieter; Lynes, Michael A; Waeytens, Anouk; Cuvelier, Claude; Vos, Filip De; Vanhove, Christian; Vos, Martine De; Laukens, Debby
Abstract Inflammatory bowel diseases (IBDs) are recurrent intestinal pathologies characterized by a compromised epithelial barrier and an exaggerated immune activation. Mediators of immune cell infiltration may represent new therapeutic opportunities. Metallothioneins (MTs) are stress‐responsive proteins with immune‐modulating functions. Metallothioneins have been linked to IBDs, but their role in intestinal inflammation is inconclusive. We investigated MT expression in colonic biopsies from IBDs and acute infectious colitis patients and healthy controls and evaluated MT's role in experimental colitis using MT knockout mice and anti‐MT antibodies. Antibody potential to target extracellular MT and its mechanism was tested in vitro. Biopsies of patients with active colitis showed infiltration of MT‐positive cells in a pattern that correlated with the grade of inflammation. MT knockout mice displayed less severe acute dextran sulphate sodium (DSS)‐induced colitis compared to congenic wild‐type mice based on survival, weight loss, colon length, histological inflammation and leukocyte infiltration. Chronic DSS‐colitis confirmed that Mt1 and Mt2 gene disruption enhances clinical outcome. Blockade of extracellular MT with antibodies reduced F4/80‐positive macrophage infiltration in DSS‐ and trinitrobenzene sulphonic acid‐colitis, with a tendency towards a better outcome. Whole‐body single‐photon emission computer tomography of mice injected with radioactive anti‐MT antibodies showed antibody accumulation in the colon during colitis and clearance during recovery. Necrotic and not apoptotic cell death resulted in western blot MT detection in HT29 cell supernatant. In a Boyden chamber migration assay, leukocyte attraction towards the necrotic cell supernatant could be abolished with anti‐MT antibody, indicating the chemotactic potential of endogenous released MT. Our results show that human colitis is associated with infiltration of MT‐positive inflammatory cells. Since antibody blockade of extracellular MT can reduce colitis in mice, MT may act as a danger signal and may represent a novel target for reducing leukocyte infiltration and inflammation in IBD patients. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd